Clinical and electrocardiographic markers of trimetazide effectiveness in patients with Functional Class II-III effort angina - Yu. N. Fedulaev; I. M. Korochkin (Российский кардиологический журнал, 2007)
In total, 156 patients with Functional Class (FC) II-III effort angina (EA) received standard therapy (beta-adrenoblockers, ACE inhibitors, disaggregants) plus trimetazide (60 mg/d) for 16 weeks. Control group included 40 patients with FC II-III EA, receiving standard therapy only. Combined therapy was associated with: nitroglycerine dose reduction; physical stress tolerance increase; decrease of qualitative and quantitative signs of pain and painless myocardial ischemia, supraventricular and ventricular extrasystoles, QC dispersion; increase in timely and spectral parameters of heart rate variability.